Anxiety and Its Associated Factors During the Initial Phase of the COVID-19 Pandemic in Indonesia - Anindyajati, Gina; Wiguna, Tjhin; Murtani, Belinda Julivia; Christian, Hans; Wigantara, Ngurah Agung; Putra, Anggi Aviandri; Hanafi, Enjeline; Minayati, Kusuma; Ismail, Raden Irawati; Kaligis, Fransiska; Savitri, Ary I.; Uiterwaal, Cuno S. P. M.; et al. (Frontiers in Psychiatry, 2021)
Introduction: Coronavirus disease 2019 (COVID-19) is caused by a novel coronavirus which has not been identified previously in humans. The disease leads to respiratory problems, systemic disorders, and death. To stop the virus transmission, physical distancing was strongly implemented, including working and school from home (WFH & SFH). The limitation altered daily routines and needs advanced to adapt. Many have felt uncomfortable and this could have triggered anxiety symptoms. This study aimed to evaluate the proportion of significant anxiety symptoms and its association with COVID-19-related situations in an Indonesian context during the initial months of the pandemic. Methods: An online community survey was distributed through social media and communication platforms, mainly WhatsApp, targeting people >18 years old in Indonesia. Anxiety symptoms were assessed using Generalized Anxiety Disorder-7 (Indonesian Version). Demographical data and information on social situation related to the COVID-19 pandemic were collected. The proportion of clinically significant anxiety symptoms was calculated and the association with demographic and social factors was assessed using chi square test (χ2) and logistic regression for multivariate analysis. Results: Out of 1215 subjects that completed the survey, 20.2% (n = 245) exhibited significant anxiety symptoms. Several factors, such as age (AOR = 0.933 CI 95% = 0.907–0.96), sex (AOR = 1.612 CI 95% = 1.097–2.369), medical workers (AOR = 0.209 CI 95% = 0.061–0.721), suspected case of COVID-19 (AOR = 1.786 CI 95% = 1.001–3.186), satisfaction level of family support (AOR = 3.052 CI 95% = 1.883–4.946), and satisfaction level of co-workers (AOR = 2.523 CI 95% = 1.395–4.562), were associated with anxiety. Conclusion: One out of five Indonesian people could have suffered from anxiety during the COVID-19 pandemic. The riskiest group being young females, people who had suspected cases of COVID-19, and those with less satisfying social support. Nevertheless, health workers were found to have a lesser risk of developing anxiety. Accessible information and healthcare, social connection, supportive environment, and mental health surveillance are important to prevent bigger psychiatric problems post-pandemic.